Indigenous People "VIS-A-VIS" Participatory Natural Resource Management - Shukla, Gopal; Koul, Divy Ninad; Chakravarthy, Sumit (Indian Forester, 2014)
Indigenous people have high dependency on natural resources and hence they have high interaction with the natural resources.Efforts done by local communities to conserve their natural resource not only aids their livelihood but also supports ecosystem as a whole. The degree of sustainability in resource use is dependent on the indigenous people’s knowledge, culture, values, norms and capacity to act and organize them. The present paper highlights the problems and challenges faced by the indigeous peoples. It also makes suggestions on how to expand the deepen partnerships with governments and others for conservation of natural resources and at the same time upliftment of indigenous people. As most indigenous peoples live in marginal areas assisting indigenous people in overcoming their poverty and to contribute to sustainable development is essential. The Crucial role of indigenous people for biodiversity conservation and sustainable development has recently received a lot of attention. Although much progress has been made, much remains to be done in thos area.